LEGAL PROBLEMS REGARDING ‘CERTIFIED COPY’ IN PROFESSION OF CERTIFIED TRANSLATORS - DE LEGE LATA AND DE LEGE FERENDA - LITWIN, Katarzyna; SZPYT, Kamil (Comparative Legilinguistics, 2012)
This paper presents a problematical issue regarding the right of a legal translator to „execute certified copies of documents drawn up in a foreign language, verify and certify copies of documents drawn up in a foreign language and prepared by another person”. After a brief commentary concerning the development of the institution and the sources of this right in other modern regulations, the meaning of the term ‘certified copy’ is discussed in the light of other binding legal acts. The term ‘certified copy’ used in relation to the profession of a certified translator under the Act on the profession of certified translators and the Regulation of the Minister of Justice on certified translators’ fee, and profession of a notary in the Act on Notary Public Law and the Regulation of the Minister of Justice on the maximum notaril fee are discussed. Finally, recommendations concerning proposed legislative changes and conclusions are presented.